Pengembangan Media Scrapbook 3D pada Pembelajaran Tema 6 Kelas III SD Negeri 2 Mulyo Rejo - Binti Nurmala; Maharani Oktavia; Kiki Aryaningrum (Journal on Education, 2023)
The research objective was to develop 3D Scrapbook learning media in order to determine the validity and practicality of the developed 3D Scrapbook media. The type of research used is Research and Development (R&D) with the ADDIE method which consists of analysis, design, development, implementation, evaluation. The results of the 3D scrapbook learning media research were declared valid as indicated by the validation results by the validator obtaining an average percentage of 84.9% with a very decent category. Assessment of student responses in small groups obtained an average percentage of 92.8% with very practical criteria, and large groups obtained an average percentage of 94.9% with very practical criteria. The conclusion is that the developed 3D Scrapbook learning media on the theme of 6 class III in SD is very feasible, very practical.